2019
DOI: 10.15376/biores.14.3.6501-6515
|View full text |Cite
|
Sign up to set email alerts
|

Efficient fractionation of corn stover by bisulfite pretreatment for the production of bioethanol and high value products

Abstract: Fractionation of corn stover (CS) was carried out by bisulfite pretreatment in order to improve the production of bioethanol and high-value chemicals. Firstly, the optimum bisulfite pretreatment conditions of CS (170 C, 30 min, 7% NaHSO3, 1% H2SO4) were identified. Next, a biorefinery process of bisulfite pretreatment for CS was proposed. CS was separated into solid and liquor components using such pretreatment. The solid components were employed for bioethanol production by quasi-simultaneous saccharificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The CS was pretreated with 7% sodium bisulfite and 1% sulfuric acid at 170 °C for 30 min as described in a previous publication (Tan et al 2019). Table 1 lists the chemical compositions of the CS before and after the acid sulfite pretreatment, as well as the enzymatic conversion rates of glucan and xylan in the untreated and pretreated CS.…”
Section: Chemical Compositions and Enzymatic Hydrolysis Efficiencies ...mentioning
confidence: 99%
See 3 more Smart Citations
“…The CS was pretreated with 7% sodium bisulfite and 1% sulfuric acid at 170 °C for 30 min as described in a previous publication (Tan et al 2019). Table 1 lists the chemical compositions of the CS before and after the acid sulfite pretreatment, as well as the enzymatic conversion rates of glucan and xylan in the untreated and pretreated CS.…”
Section: Chemical Compositions and Enzymatic Hydrolysis Efficiencies ...mentioning
confidence: 99%
“…Hemicelluloses can be partially degraded or dissolved under acidic conditions. The sulfite, bisulfite, and sulfur dioxide can attack the Cα or Cγ position of lignin (i.e., sulfonation reactions), which can increase the hydrophilicity of the lignin, which promotes its dissolution (Tan et al 2016;Liu et al 2018;Ren et al 2018;Tan et al 2019). In the present study, the acid sulfite pretreatment caused a 75.08% loss of xylan and a 33.98% loss of lignin, which suggested that both of them were degraded or dissolved to some extent during the process.…”
Section: Chemical Compositions and Enzymatic Hydrolysis Efficiencies ...mentioning
confidence: 99%
See 2 more Smart Citations
“…11 In this context, not only in Brazil but worldwide, several residues are being investigated in order to meet the growing demand for second-generation ethanol. 12 A successful example was work by Reina et al 13 in obtaining lignocellulosic ethanol from Eucalyptus dunnii bark. Using an innovative ionic liquid pretreatment process, the authors reached 70% of ethanol yield, a result fourfold higher than the one obtained using the bark without pretreatment.…”
mentioning
confidence: 99%